2015
DOI: 10.1017/s1473550415000130
|View full text |Cite
|
Sign up to set email alerts
|

Calbindin-D28k immunoreactivity in the mice thoracic spinal cord after space flight

Abstract: The aim of the work was to analyse changes in the location and morphological characteristics of calbindin (CB)-immunoreactive (IR) neurons of the thoracic spinal cord of C57BL/6N male mice after completion of a 30-day space flight on board the BION-M1 biosatellite (Russia, 2013). Space flight induced multidirectional changes of the number and morphological parameters of CB-positive neurons. The number of IR neurons increased in laminae I (from 10 to 17 neurons per section), II (from 42 to 67 cells per section)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Finally, our first priority was to rapidly extract the tissues to minimize the freezethaw cycle. Nevertheless, previous studies reported insignificant change in body weights of mice after space travels (32,33) and after exposing mice to hindlimb unloading on the ground. (34) Altered calcium usage, decreased mtDNA CNs, and inhibited tricarboxylic acid (TCA) cycles are likely to converge to impair mitochondrial function, because these are causally related to essential cellular metabolism.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Finally, our first priority was to rapidly extract the tissues to minimize the freezethaw cycle. Nevertheless, previous studies reported insignificant change in body weights of mice after space travels (32,33) and after exposing mice to hindlimb unloading on the ground. (34) Altered calcium usage, decreased mtDNA CNs, and inhibited tricarboxylic acid (TCA) cycles are likely to converge to impair mitochondrial function, because these are causally related to essential cellular metabolism.…”
Section: Discussionmentioning
confidence: 84%
“…Finally, our first priority was to rapidly extract the tissues to minimize the freeze‐thaw cycle. Nevertheless, previous studies reported insignificant change in body weights of mice after space travels ( 32,33 ) and after exposing mice to hindlimb unloading on the ground. ( 34 )…”
Section: Discussionmentioning
confidence: 97%
“…We also observed changes in the number of CB‐immunoreactive (IR) neurons in the SC after a sensory deficit was induced by space flight (Porseva et al, 2015, 2017). The neurotoxic effect of capsaicin is also explained by the excessive intracellular accumulation of Ca 2+ and Na + ions, which leads to protease activation and cell death (Hwang et al, 2021; Jin et al, 2005).…”
Section: Introductionmentioning
confidence: 81%
“…Numerous unmyelinated fibers run from one half of the gray matter of the SC to the other, especially dorsally from the central canal, where the CAA is located. This suggests an integrative and coordinating function, which is typical for the entire intermediate zone of the SC with interneurons of different functional specifications (Deuchars et al, 2005; Porseva et al, 2015).…”
Section: Discussionmentioning
confidence: 99%